From Voltage to Wiring: Synaptic connectivity inference from neural voltage recordings - Fiers, Tomas (2024)
Systems neuroscience studies the links between (1) an animal’s behaviour, (2) the activity of its neurons, and (3) how these neurons are connected. Currently, only the first two can be observed simultaneously, using 'in vivo' recordings of neural activity. Observing the connections between neurons, on the other hand, requires brain slice imaging, which can only be done post-mortem. However, we might be able to *infer* the connectivity in-vivo, based on neural activity recordings. Historically, this has only been attempted using spike-timing data, with limited success.